2022
DOI: 10.1177/15910199221121378
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of young patients following mechanical thrombectomy for stroke: A systematic review and meta-analysis

Abstract: Background Young patients experience acute ischemic stroke (AIS) at much lower rates than their older counterparts. We performed a systematic review and meta-analysis to assess the question regarding outcomes and clinical characteristics of young stroke patients who underwent mechanical thrombectomy for AIS. Methods Following PRISMA guidelines, a systematic review of the literature was conducted using the databases PubMed, MEDLINE, and Embase. The primary outcome of interest was 90-day modified Rankin Scale (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…Patients with AF also tend to be older, and it has been previously shown that younger patients have better outcomes following MT for AIS . All studies in our systematic review and meta-analysis reported that patients with AF were older than their counterparts without AF, which is consistent with patients with AF in general.…”
Section: Discussionsupporting
confidence: 81%
“…Patients with AF also tend to be older, and it has been previously shown that younger patients have better outcomes following MT for AIS . All studies in our systematic review and meta-analysis reported that patients with AF were older than their counterparts without AF, which is consistent with patients with AF in general.…”
Section: Discussionsupporting
confidence: 81%
“…After analyzing data from 5 multicenter observational studies including a total of 3,384 patients treated with EVT within 6-24 hours from symptom onset, they found comparable rates of 3-month functional independence and symptomatic intracranial hemorrhage between those selected by noncontrast CT and those selected by CTP. 7 However, patients selected by CTP were found to have a 31% higher likelihood of postprocedural successful reperfusion and a 21% lower odds for mortality at 3 months. 7 The findings in this meta-analysis by Kobeissi et al derive from observational studies, which are prone to confounding.…”
mentioning
confidence: 95%
“…7 However, patients selected by CTP were found to have a 31% higher likelihood of postprocedural successful reperfusion and a 21% lower odds for mortality at 3 months. 7 The findings in this meta-analysis by Kobeissi et al derive from observational studies, which are prone to confounding. The lower mortality of patients selected by CTP compared with those selected by noncontrast CT could be related to selection bias in favor of the group selected by CTP, a notion that, however, is not further supported by the lack of difference in functional outcomes between the 2 groups.…”
mentioning
confidence: 95%
See 2 more Smart Citations